Self-care practices on hypertension: Prevalence and predictors in Puducherry, South India - Chandru Sivamani; Ganesh Kumar Saya; Revathi Ulaganeethi; Palanivel Chinnakali (Clinical Epidemiology and Global Health)
Background: Self-care practices plays an important role in reducing the mortality and morbidity associated with hypertensive complications. Therefore, this study aimed to assess poor self-care practices on hypertension and its predictors among patients attending the non-communicable disease clinics in urban and rural primary healthcare settings in Puducherry, South India. Methods: A cross-sectional analytical study was conducted among people with hypertension aged ≥18 years from September to December 2023. Systematic random sampling technique was used to recruit the participants. The data on self-care practices were captured using the “Hypertension Self-Care Activity Level Effects (H-SCALE)” questionnaire. The subscales were medication adherence, low-salt diet, physical activity, smoking, alcohol and weight management. Participants who adhered <4 out of six subscales of H-SCALE, was considered as poor self-care practices. Multivariable analysis was carried out to adjust for potential covariates, and adjusted prevalence ratio with a 95 % confidence interval was reported. Results: Out of 267 participants with hypertension, 158 (59.2 %) were >60 years of age and 182 (68.2 %) were females. About 79 (29.6 %) had poor self-care practices. Among 267, 63 (23.6 %) had uncontrolled hypertension and it was more among those with poor self-care practices (46.1 % Vs 24.5 %). After adjusting for co-variates, urban residents (APR: 1.7, 95 % CI: 1.1–2.4, p = 0.004) and uncontrolled hypertension status (APR: 1.8, 95 % CI: 1.1–2.4, p < 0.001) were significantly associated with poor self-care practices. Conclusion: More than one-fourth of the participants with hypertension had poor self-care practices and it was significantly higher in participants with uncontrolled hypertension.